PENGARUH MODELPROBLEM BASED LEARNING DAN COOPERATIVE LEARNING TIPE THINK PAIR SHARE TERHADAP PRESTASI BELAJAR IPA DITINJAU DARI MINAT SISWA KELAS V SD KECAMATAN BULUKERTO TAHUN PELAJARAN 2012/2013 - RIKA YUNI AMBARSARI (JURNAL MITRA SWARA GANESHA, 2014)
The purpose of this study was to investigate: (1) Whether    use of   model Problem Based Learning, and  Think Pair Share method have positive correlation  towards the students' learning outcomes of of Natural Sciences, (2) whether students' different levels of interest (high, medium, and low interest) affects the learning outcomes , (3) whether there is a positive corelation   between  Problem Based Learning and  Think Pair Share,  students' interest, and of the learning outcomes of Natural Science.The method used in this research was experimental research. The populations  in this study were  all elementary school students in  Bulukerto District, Wonogiri Regency, whereas  the sub-populations  were the fifth grade students in Bulukerto District Elementary School  academic year 2012/2013. The sample of the research was collected by using  multistage cluster random sampling. Questionnaires were used to investigate the students' interest, while test was used to measure students' learning outcomes . The data was analyzed by using two-way analysis method..Based on those results, it can be concluded that: (1) There is  a positive effect of using the models Problem Based Learning and Coperative type Think Pair Share the Natural Sciences towards the students' learning  outcomes (F count> F table or 15,48> 4.07), (2) Students' different levels of interest (low, medium, and high interest) affect the learning outcomes of Natural Science  (F count > F table or 17,7281>3,21), (3) There is not positive correlation between  Problem Based Learning and Cooperative learning types Think Pair Share,  students' interest, and students'  learning outcomes of Natural Sciences (F count > F table or 2,36<3,21).Based on the  study, it is expected that teachers will able to implement the most suitable method in the learning process. . Teachers should work hard to increase students' interest, because the learning method and student interest will affect the learning outcomes.